2008
DOI: 10.1116/1.2932100
|View full text |Cite
|
Sign up to set email alerts
|

System-level line-edge roughness limits in extreme ultraviolet lithography

Abstract: As critical dimensions shrink, line edge and width roughness (LER and LWR) become of increasing concern. Traditionally LER is viewed as a resist-limited effect; however, as critical dimensions shrink and LER requirements become proportionally more stringent, system-level effects begin to play an important role. Recent advanced EUV resist testing results have demonstrated lower bounds on achievable LER at the level of approximately 2 to 3 nm. Here we use modeling to demonstrate that a significant portion of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…As demonstrated by the modeled mask-induced LER data in Table 1 (see Ref. [4] for details on the modeling procedure), coherence and defocus parameters have a more significant impact on image LER coupling coming from phase roughness on the mask rather than mask absorber LER. Note that defocus has a more significant impact with annular illumination for both sources of mask-induced LER.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by the modeled mask-induced LER data in Table 1 (see Ref. [4] for details on the modeling procedure), coherence and defocus parameters have a more significant impact on image LER coupling coming from phase roughness on the mask rather than mask absorber LER. Note that defocus has a more significant impact with annular illumination for both sources of mask-induced LER.…”
Section: Resultsmentioning
confidence: 99%
“…Recent modeling results [4] have suggested that mask effects are indeed important In advanced EUV development tools such as the SEMA TECH Berkeley microfield exposure tool (BMET) [5]. Here we present the first resist-based measurements of such effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mask contributors, especially multilayer phase roughness have recently been shown to be significant contributors to LER [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Since this effect has been experimentally verified [5], there has been significant interest in the implications it has on EUV mask phase roughness specifications and thus substrate roughness specifications. This question has been addressed in the past [6] using two dimensional (2D) scalar modeling with the thin mask approximation [4] yielding the stringent specification of 50 pm replicated surface roughness [6] for 22-nm half-pitch device fabrication. Thin mask modeling was used due to the significant memory and speed burdens that would be incurred with full three dimensional finite-difference time-domain (FDTD) modeling.…”
Section: Introductionmentioning
confidence: 99%